Perilaku Penggunaan Kontrasepsi IUD Di Kecamatan Sukmajaya Depok: Sebuah Penelitian Kualitatif - Maria Gayatri (STIKes Hang Tuah Pekanbaru, 2019)
A qualitative research through Rapid Assessment Procedure on the Behavior of Intrauterine Device (IUD) use was carried out in Sukmajaya District, Depok. The aims of this research ware to analyxe predisposing, enabling and reinforcing factors influencing the use of IUDs. The informants were mother who use IUD, mother who ever use IUD and mother who use non-IUD methods (such as pills and injectables). The results showed that the informants understood IUD effective methods to prevent pregnancy. Most informants considered that IUDs were cheap, available at health facilities and the service given by competence providers. Support from husband, encouragement from friends who successfully used the IUD and the effectivity and reversibility of IUDs were also as strength factors for IUDs use. However, there were some factors that inhibit the use of IUDs such as side effects, rumors of IUDs, incomplete counseling from providers and sharing negative experiences of friend who have failed to use IUD. In conclusion, IUD used was influenced by multi-factors such as predisposing factors (knowledge, values, beliefs, attitude of perception), enabling factors (access to information, availability of IUDs, officer competencies, regulations) and reinforcing factors (husband, friends, health workers).